The effect of sex and irritable bowel syndrome on HPA axis response and peripheral glucocorticoid receptor expression. (July 2016) - Videlock, Elizabeth J.; Shih, Wendy; Adeyemo, Mopelola; Mahurkar-Joshi, Swapna; Presson, Angela P.; Polytarchou, Christos; Alberto, Melissa; Iliopoulos, Dimitrios; Mayer, Emeran A.; Chang, Lin
Highlights: Cortisol response to ACTH is affected by sex and irritable bowel syndrome (IBS). Response is increased in men but blunted in women with IBS compared to controls. Glucocorticoid receptor α (GRα) mRNA is reduced in IBS and negatively correlates with ACTH response. Low expression of GRα is associated with increased symptom severity in IBS. Abstract: Background and aims: Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis has been reported in irritable bowel syndrome (IBS). Enhanced HPA axis response has been associated with reduced glucocorticoid receptor (GR) mediated negative feedback inhibition. We aimed to study the effects of IBS status, sex, or presence of early adverse life events (EAL) on the cortisol response to corticotropin-releasing factor (CRF) and adrenocorticotropic hormone (ACTH), and on GR mRNA expression in peripheral blood mononuclear cells (PBMCs). Methods: Rome III+ IBS patients and healthy controls underwent CRF (1 μg/kg ovine) and ACTH (250 μg) stimulation tests with serial plasma ACTH and cortisol levels measured (n = 116). GR mRNA levels were measured using quantitative PCR (n = 143). Area under the curve (AUC) and linear mixed effects models were used to compare ACTH and cortisol response measured across time between groups. Results: There were divergent effects of IBS on the cortisol response to ACTH by sex. In men, IBS was associated with an increased AUC (p = 0.009), but in women AUC was blunted in IBS (p = 0.006). Men also had reduced GR mRNA expression (p = 0.007). Cumulative exposure to EALs was associated with an increased HPA response. Lower GR mRNA was associated with increased pituitary HPA response and increased severity of overall symptoms and abdominal pain in IBS. Conclusion: This study highlights the importance of considering sex in studies of IBS and the stress response in general. Our findings also provide support for PBMC GR mRNA expression as a peripheral marker of central HPA response.